Simple $D [X, Y; \sigma, а]$-modules - Bavula , V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The article classifies simple modules over a generalized Weyl algebra of degree 1 with basis ring $D$ that is a commutative domain with limited minimality condition.